Shielding performance of debris shield with separated rear wall. (March 2020) - Xuezhong, Wen; Jie, Huang; Zhaoxia, Ma; Junyao, Zhao; Fawei, Ke; Jingui, Qin; Lin, Jiang; Jing, Li; Sen, Liu
Highlights: Separated rear wall (SRW) shield was investigated by hypervelocity impact test and simulation. The peak velocity on the back surface of rear wall in SRW shield is lower than that in Whipple shield. The damage of rear wall in SRW shield can be reduced effectively. The performance of SRW shield is better than that of Whipple shield. Abstract: Generally, changing the properties of bumper or the stuffed wall in a debris shield is the traditional method to improve shielding performance. A new way to improve shielding performance by separating the rear wall of debris shield was explored in this paper. Both hypervelocity impact tests and simulations were performed to evaluate the performance of the shield with a separated rear wall. The projectiles were aluminum spheres with a diameter of 6.0 mm at the impact velocity of about 8.3 km/s, and a diameter of 4.0 mm at the impact velocity of about 4.7 km/s. The targets were the separated rear wall shield (SRW) and Whipple shield with the same areal density. The results show that the shielding performance of a SRW shield is improved and better than that of a Whipple shield with the same areal density, because the separated surface in SRW shield can attenuate the propagation of the impact energy wave, decrease the free surface velocity on the back of the rear wall, and then reduce the damage on the rear wall.